Inpatient psychiatric treatment is not always effective in adolescent sample. (2nd January 2018) - Remberk, Barbara; Bażyńska, Anna Katarzyna; Brągoszewska, Joanna; Niwiński, Piotr; Piróg-Balcerzak, Agnieszka; Popek, Lidia; Rybakowski, Filip
Abstract: Objective: Numerous studies confirm efficacy of psychiatric treatment as well as psychiatric placebo. The aim of the current study was the assessment of improvement rate and factors associated with treatment response in naturalistic group of adolescent inpatients. Methods: Eighty two consecutive adolescent inpatients were recruited. Each patient at the admission and discharge was assessed with brief psychiatric rating scale (BPRS), eating attitude test (EAT-26), clinical global impression scale (CGI-S) and children global assessment scale (CGAS). Individual and family history was assessed by semi-structured interview. Patients, who improved in at least two interviewer-based scales (IMP, n  = 67) were compared to the rest (N-IMP, n  = 15). For statistical analysis STATISTICA package was used. Results: The main difference between groups was ICD-10 diagnosis distribution: in the IMP group more anxiety-related disorders (F4), in the N-IMP group more personality disorders (F6). Other differences include history of paediatric hospitalisations and surgery (more in the N-IMP group). Most of the analysed factors did not differ between groups. Conclusions: The inpatient treatment seems to be most effective in severe mental states and in anxiety-related disorders and least effective in personality disorders. Due to limited inpatient treatment efficacy we believe outpatients services are crucial in adolescent psychiatry.